The Influence of Fly Ash on the Compressive Strength of Recycled Concrete Utilizing Coarse Aggregates from Demolition Works - Phan, V. T.; Nguyen, T. H. (Engineering, Technology & Applied Science Research, 2021)
The compressive strength of recycled concrete with coarse aggregates with and without fly ash was studied in this paper. The recycled concrete was designed to have a compressive strength of Rn=15Mpa. The ratio of conventional aggregates and recycled coarse aggregates was 50-50. Fifteen samples for each recycled concrete aggregate had been cast and were tested 7, 14, and 28 days after curing. The experimental results indicate that the strength development of the two recycled concrete mixes is relatively uniform. Fly ash increased the compressive strength of recycled concrete by 11% for 7-day aged samples. The recycled concrete with fly ash had 7% less compressive strength than the concrete consisting of natural aggregates.